Families of functions with equal-power absolutely continuous integrals - Dovgoshei , A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The approximation of functions from Hardy classes by bounded analytic functions is investigated. A theorem is proved, characterizing the sets of functions with equiabsolutely continuous integrals as limit points of the family of bounded subsets of the space Н∞.